A value-added analysis of trade in Taiwan and Korea's ICT industries. (7th March 2016) - Lin, Hsing-Chun; Hsu, Shih-Hsun; Liou, Ruey-Wan; Chang, Ching-Cheng
Abstract : Purpose: – The purpose of this paper is to extricate value-added exports in information and communications technology (ICT) industry earned by Taiwan and Korea. Additionally, the authors decompose Taiwan and Korea's gross exports into various meaningful components. Design/methodology/approach: – The authors use the inter-country input-output (ICIO) table which endows with cost structures of industries as well as trade information, facilitating in keeping track of the flow of products and value-added. The ICIO table used in this paper comes from the World Input-Output Database. The authors also use the way Wang et al. (2013) decomposed the intermediate goods exports into various components to provide further insights. Findings: – The empirical results indicate that Taiwan and Korea's ICT export to the world shrink by 47.8 and 40.9 percent when the trades are measured in value-added terms. Taiwan and Korea's ICT export will also decrease by 75.1 and 57.8 percent. From the viewpoint of value added in trade, the share of value added embodied in Taiwan and Korea's gross ICT exports continued to decrease and reached 24.9 and 42.2 percent in 2011, while the components of pure double counted terms kept growing in recent years. Originality/value: – With global value chains flourishing in recent years, conventional trade statistics not only fails to highlight the vertical specialization among different countries, but also distorts the measurement of a country's competitiveness. This paper extricates value-added exports in ICT industry earned by Taiwan and Korea and bring into focus the importance of trade in value added.